PENILAIAN KINERJA KOPERASI UNIT DESA (KUD) PENEBEL TABANAN DENGAN PENDEKATAN BALANCED SCORECARD - I Gede Putu Banu Astawa; I Putu Julianto; Luh Gede Kusuma Dewi (Monex: Journal of Accounting Research, 2020)
The study aimed to find out how the Penebel Tabanan Village Unit Cooperative Performance Assessment (KUD) with the Balanced Scorecard Approach. The purpose of this study is to determine the performance of Penebel Tabanan Village Unit Cooperatives (KUD) when measured using the Balanced Scorecard approach. This type of research is descriptive research. The data collection method used is the case study method at Penebel Tabanan Village Unit Cooperative (KUD). Data collection techniques are interviews or interviews, and documentation. The data analysis procedure used is calculating four perspectives on the Balanced Scorecard, namely: financial perspective, customer perspective, internal business process perspective and learning and growth perspective. Based on the results of the measurement of cooperative performance, it shows that from a financial perspective for 2015 to 2018 it is 37.9465. Assessment for the overall score on the customer's perspective from 2015 to 2018 is 18,508. For the perspective of internal business processes from 2015 to 2018, this can be seen from the increase or achievement of targets in the process of innovation, operations, and after-sales services that are met or achieved with the total score obtained is 10. And for learning and growth perspectives from from 2015 to 2018 cooperatives amounted to 16.07. So the overall results of the Penebel Tabanan Village Unit Cooperative (KUD) performance appraisal with a total score of performance appraisal is 82.5245, so that it has a good reputation for cooperative performance during the testing period. Keywords: Cooperative Performance, Balanced Scorecard, Village Unit Cooperative   (KUD).